(untitled) (Journal of Nepal Physical Society, 2020)
Two dimensional materials show multiple applications including in semiconductor devices and gaseous storage. We have carried out First-Principles calculations to study the geometrical structures, stability and electronic/magnetic properties of pristine as well as double vacancy phospherene. Calculations are based on Density Functional Theory (DFT) taking an account of van der Waals (vdW) interaction in the DFT-D2 approach within Generalized Gradient Approximation (GGA). Modeling and simulation have been performed with Quantum ESPRESSO (QE) codes. The supercell of 4×4 structure, whose building block is an orthogonal unit cell with four phosphorous atoms, is used to model the samples. Based on the stability of defected single layer phosphorene, a couple of structures (DV(5|8|5)-1 and DV(5|8|5)-2) have been considered to calculate their formation energy, band structure and other properties. Formation energy values find the former structure (DV(5|8|5)-1) more favorable to create than the later one. A band gap of 0.86eV for pristine phospherene, an excellent agreement with the experiment, validates the results of present calculations. The phosphorene with double vacancy, however, shows significant changes in electronic bands with reference to the pristine one. The band gap for DV(5|8|5)-1 and DV(5|8|5)-2 systems are found to be 1.01eV and 0.1 eV respectively. No magnetic moment in both the pure and defected (double vacancy) phospherene monolayer approves that only the vacancies are not enough to induce magnetic properties in phosphorene.